The Effect of Cash Flow on Stock Returns in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Suci Putri Astiti; Sufardi Sufardi; Alfitha Putri Irfan (CV. Sakura Digital Nusantara, 2025)
This research aims to analyze the influence of cash flow on stock returns in property and real estate companies listed on the Indonesian Stock Exchange. This research method uses a quantitative approach. Hypothesis testing uses SPSS version 26 which consists of Cash Flow as the independent variable and Stock Returns as the dependent variable. The data collection technique is a purposive sampling technique. The population in this research is all Property and Real Estate companies listed on the Indonesia Stock Exchange, totaling 92 companies. Meanwhile, the sample in this study consisted of 5 companies that met the criteria. This research was conducted from June to July 2024. After data analysis, the research results show that the variable (X1) operating cash flow is (-13,581<1.75). This result shows that operating cash flow has a negative and significant effect on stock returns, meaning that H1 is rejected. The research results of the variable (X2) investment cash flow (39.644>1.75) show that investment cash flow has a positive effect on stock returns, meaning that H2 is accepted. And the research results of the variable (X3) funding cash flow (3.560>1.75) these results show that funding cash flow has a positive and significant effect on stock returns, meaning that H2 is accepted.